A Study of English Article Choice: A Case Study of Two Indonesian English Teachers - Sondari, Parawati Siti (2015)
This study attempts to look into the article choice of a/an, the, and Ø and their production by two Indonesian English teachers. The participants of this study, i.e. teacher 1 and teacher 2, are two experienced Indonesian English teachers with different proficiency levels, i.e. upper-intermediate and advanced respectively. The primary data collection instrument was a forced-choice elicitation task adopted from Ionin, Ko, and Wexler (2004), Snape (2006), and White (2009) controlled in its noun types and semantic contexts of definiteness [+def] and specificity [+spec]. Furthermore, the article production of the teachers in the classrooms was observed and video-taped. Based on the findings, both teachers have acquired definite article the yet have shown variability in their use of a/an and Ø as suggested by both the forced-choice elicitation task and the observation data. They could consistently produce accurate the in most cases yet the uses of a/an and Ø were contrastingly different in the two sources of data. In addition, teacher 1 substantiated the flooding and more omission errors of a/an, while teacher 2 demonstrated more comission errors of overusing a/an. In terms of specificity, based on the two data sources, both participants demonstrated that their article choice indicated very low fluctuation, thus, specificity still plays a role in the participants article choice. In addition, there are other uses in which both participants overused the in [+def,+spec] contexts and a/an or Ø in [-def,-spec] contexts indicating that the participants have not fully acquired (in)definiteness in their article choice (Humphrey, 2007). In terms of noun countability in the two sources of data, teacher 1 demonstrated that the four types of nouns contributed to misidentification to his article production, i.e. abstract singular nouns, mass nouns, imaginable singular nouns, and imaginable plural nouns. Meanwhile, teacher 2 showed that three types of nouns, i.e. abstract singular nouns, imaginable singular nouns, and mass nouns, contributed misidentification to her use of articles.